열화한 STS316L에 대한 Cr-free 코팅액의 내식특성 - 이소영(So-Young Lee); 김영수(Young-Soo Kim); 정희록(Hee-Rock Jeong); 안석환(Seok-hwan Ahn); 남기우(Ki-Woo Nam) (Han-guk haeyang gonghak hoeji (Online), 2015)
In this study, we developed a Cr-free organic/inorganic hybrid solution and investigated its coating properties on degraded STS316L. Both the OIBD-1 solution and OIBD-2 solution had excellent corrosion resistance and adhesion ability. However, the solution had some problems in a boiling water environment. In addition, the flexibility was excellent, and the scratch resistance was relatively good.